Bruxism Associated with Anoxic Encephalopathy: Successful Treatment with Baclofen - A. Bruce Janati; Naif Saad ALGhasab; Fahad Saad ALGhassab (Case Reports in Dentistry)
Introduction. Bruxism is a movement disorder characterized by grinding and clenching of the teeth. Etiology of bruxism can be divided into three groups: psychosocial factors, peripheral factors, and pathophysiological factors. Methods. The clinical investigation was conducted at King Khaled Hospital in Hail, Saudi Arabia, in 2012. Results. A 16-year-old Saudi female was brought to the hospital in a comatose state and with generalized convulsive seizures secondary to acute anoxic encephalopathy. In the third week of hospitalization, while still in a state of akinetic mutism, she developed incessant bruxism which responded favorably to a GABA receptor agonist (baclofen). Conclusion. Our data support the hypothesis that bruxism emanates from imbalance or dysregulation of the neurotransmitter system. Larger scale studies will be needed to confirm this hypothesis.